An Experimental Study on Mechanical Behavior of Nanographene/Epoxy Nanocomposites - Altan, Mihrigul; Uysal, Alper (WILEY-HINDAWI, 2018)
Nanocomposites draw attention from many various fields and areas of usage increase with the improvement of their properties. For this purpose, nanographene particles have used to enhance the mechanical, thermal, and electrical properties. In the presented experimental study, nanocomposites were fabricated by reinforcing the epoxy matrix with nanographene particles at 0.5 and 1 wt%. The dispersion of nanofillers in epoxy matrix and the tensile properties of the nanocomposites were investigated. The tensile strength and stress at break increased with nanographene particles addition and well dispersion of nanofillers in epoxy matrix was achieved.
Keywords: Mechanical properties; Nanocomposites; Nanoparticles; Engineering; Polymer Science